2021
DOI: 10.3390/ma14164431
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Human Bone Environment: Mechanical Stimuli Guide Mesenchymal Stem Cell–Extracellular Matrix Interactions

Abstract: In bone tissue engineering, the design of in vitro models able to recreate both the chemical composition, the structural architecture, and the overall mechanical environment of the native tissue is still often neglected. In this study, we apply a bioreactor system where human bone-marrow hMSCs are seeded in human femoral head-derived decellularized bone scaffolds and subjected to dynamic culture, i.e., shear stress induced by continuous cell culture medium perfusion at 1.7 mL/min flow rate and compressive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 111 publications
(117 reference statements)
0
23
0
Order By: Relevance
“…Decellularized bone scaffolds were obtained from human trabecular femoral head specimens (permission number: 187/18, University of Wuerzburg ethics committee), as previously described in. 25 , 45 Briefly, freshly thawed samples (kept at −20°C for no more than 4 months after surgery) were precisely cut in 3 mm thick slides using an electric diamond band saw (300 Exakt D64, Walter Messner, Germany) to ensure homogeneous penetration of washing solutions through the complete sample volume. Blood and residual fat material were removed by several washing cycles in water and a chloroform (288306, Sigma-Aldrich) and methanol (8388.6, Carl-Roth) mix solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decellularized bone scaffolds were obtained from human trabecular femoral head specimens (permission number: 187/18, University of Wuerzburg ethics committee), as previously described in. 25 , 45 Briefly, freshly thawed samples (kept at −20°C for no more than 4 months after surgery) were precisely cut in 3 mm thick slides using an electric diamond band saw (300 Exakt D64, Walter Messner, Germany) to ensure homogeneous penetration of washing solutions through the complete sample volume. Blood and residual fat material were removed by several washing cycles in water and a chloroform (288306, Sigma-Aldrich) and methanol (8388.6, Carl-Roth) mix solution.…”
Section: Methodsmentioning
confidence: 99%
“…This becomes even more evident when one considers cell-ECM communication (or relations) as bidirectional interactions, wherein cells constantly rebuild their surroundings, thus untimely influencing their own fate. 23 25 It follows from this that great efforts have been made in the field of tissue engineering using advanced biomaterials to recapitulate these unique niche conditions in ex vivo culture. The key universal goal is to avoid the persistently observed “ageing” process of cells during long-lasting in vitro cultivation – that is, cell shape change, and significantly decreased colony-forming and differentiation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the nitric oxide promoted the osteogenesis process by regulation of canonical Wnt/β-catenin signaling. In another study, continuous medium flow with a mean shear stress equal to 8.5 mPa improved the proliferation of human BMDSCs and increased ECM production compared to control cells cultured in static conditions [78]. In turn, Yamada et al [79] showed that during the perfusion (shear stress distribution ranging from 0.20 mPa to 0.40 mPa), cell proliferation on polyester-based scaffolds was significantly inhibited.…”
Section: Perfusion Bioreactorsmentioning
confidence: 96%
“…Perfusion bioreactors consist of a media reservoir, a pump, a flow perfusion chambers, an oxygenator, a tubing circuit, and a waste tank. Several authors reported successful use of perfusion bioreactors for BTE purposes [ 163 , 164 , 165 ]. Liu et al presented results of using porcine decellularized native bone seeded with human smooth muscle cells and human umbilical vein endothelial cells within a perfusion bioreactor.…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…Ressler et al confirmed osteogenic differentiation using a composite Calcium phosphate/Hydroxyapatite scaffold seeded with human mesenchymal stem cells in a perfusion bioreactor [ 164 ]. Pereira et al used a custom-made perfusion bioreactor system and decellularized human bone scaffolds seeded with human bone marrow-derived mesenchymal stem cells [ 165 ].…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%